2021
DOI: 10.1021/acs.energyfuels.1c00412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CO2 and Produced Gas Hydrocarbons to Recover Crude Oil from Williston Basin Shale and Mudrock Cores at 10.3, 17.2, and 34.5 MPa and 110 °C

Abstract: Carbon dioxide and hydrocarbon gases including methane, ethane, propane, and produced gas (69.5/21/9.5 mol ratio of methane/ethane/propane) were used to recover oil from rock samples collected in the Middle Bakken (MB) target drilling zone and from a Lower Bakken Shale (LBS) source rock. Experiments were designed to mimic the fracture-dominated flow expected to occur during gas injection into hydraulically fractured unconventional reservoirs such as the Bakken Petroleum System. Higher pressures recovered oil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…Factors with MMP, Oil Solubility, and the Recovery of Residual Oil from Middle Bakken Rock Samples. The same five gases and Bakken crude oil have previously been used to determine MMP 39 as well as crude oil hydrocarbon solubility 40 and the recovery of residual oil from Bakken rock samples, 41 which was performed by exposing rock cores to each gas at reservoir conditions of 110 °C and 34.5 MPa and collecting the produced oil hydrocarbons for gas chromatographic analysis, as previously described. 22,23 In general, the performance of the five test gases is similar to the results for crude oil swelling shown in Figure 6, that is, propane is superior to ethane, ethane is superior to carbon dioxide and the produced gas, and methane is the least effective.…”
Section: Comparison Of Volumetric Swellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors with MMP, Oil Solubility, and the Recovery of Residual Oil from Middle Bakken Rock Samples. The same five gases and Bakken crude oil have previously been used to determine MMP 39 as well as crude oil hydrocarbon solubility 40 and the recovery of residual oil from Bakken rock samples, 41 which was performed by exposing rock cores to each gas at reservoir conditions of 110 °C and 34.5 MPa and collecting the produced oil hydrocarbons for gas chromatographic analysis, as previously described. 22,23 In general, the performance of the five test gases is similar to the results for crude oil swelling shown in Figure 6, that is, propane is superior to ethane, ethane is superior to carbon dioxide and the produced gas, and methane is the least effective.…”
Section: Comparison Of Volumetric Swellingmentioning
confidence: 99%
“…70/20/10 mole fractions) to determine the MMP for each gas with a typical produced oil from the Middle Bakken formation, 39 measure the ability of these gases at different pressures to dissolve Bakken crude oil hydrocarbons, 40 and determine the ability of these gases (again at different pressures) to recover residual oil from both Middle Bakken siltstone and Bakken shale rock samples. 41 These laboratory studies have shown that propane is the superior gas in each of these tests, followed by ethane, then carbon dioxide and the produced gas (which have similar performance), and finally methane as the poorest EOR gas. Propane achieves MMP with Bakken crude oil at the lowest pressure, followed by ethane, carbon dioxide and the produced gas, and finally methane (which requires the highest pressure).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One strategy for producing oil from already-fractured shale wells involves injecting oil-miscible gases such as CO 2 , ethane, propane, nitrogen, or natural gas to extract the remaining oil. Of all the gases tested, CO 2 has demonstrated several advantages. CO 2 increases oil extraction by a variety of mechanisms including diffusion, vaporization, oil swelling, oil viscosity reduction, pressure support, CO 2 –oil interfacial tension (IFT) reduction, solution gas drive, and relative permeability hysteresis .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most convenient methods of utilizing this gas is to reinject it back into the reservoir as an EOR agent . Using hydrocarbon gas as an EOR agent in huff-and-puff mode could be effective in shale deposits ,, given the presence of natural fractures. ,, The efficiency of this method depends entirely on the minimum miscibility pressure (MMP) at which the associated gas achieves miscibility with the reservoir oil. Miscibility causes oil swelling and a decrease in oil viscosity.…”
Section: Introductionmentioning
confidence: 99%